2011
DOI: 10.1128/aem.00288-11
|View full text |Cite
|
Sign up to set email alerts
|

Macroscopic Biofilms in Fracture-Dominated Sediment That Anaerobically Oxidize Methane

Abstract: Methane release from seafloor sediments is moderated, in part, by the anaerobic oxidation of methane (AOM) performed by consortia of archaea and bacteria. These consortia occur as isolated cells and aggregates within the sulfate-methane transition (SMT) of diffusion and seep-dominant environments. Here we report on a new SMT setting where the AOM consortium occurs as macroscopic pink to orange biofilms within subseafloor fractures. Biofilm samples recovered from the Indian and northeast Pacific Oceans had a ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 52 publications
(72 reference statements)
1
37
0
1
Order By: Relevance
“…Similar to the samples described above, candidate bacterial phyla BHI80-139 and JS1 and lineages within the phylum Chloroflexi (i.e., Napoli-4B-65, Sh765B-AG-111, and vadinBA26) were shared between these samples, and all groups were phylogenetically related to gene clones that have previously been identified from marine sediment (e.g., Li et al, 1999;Reed et al, 2002;Newberry et al, 2004;Inagaki et al, 2006;Takeuchi et al, 2009;Briggs et al, 2011;Durbin and Teske, 2011;Hoshino et al, 2011). Candidate bacterial phylum JS1 formed the most abundant group detected (3 of 17 clones) in the near-surface squeeze cake sample from Hole U1363G (Fig.…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…Similar to the samples described above, candidate bacterial phyla BHI80-139 and JS1 and lineages within the phylum Chloroflexi (i.e., Napoli-4B-65, Sh765B-AG-111, and vadinBA26) were shared between these samples, and all groups were phylogenetically related to gene clones that have previously been identified from marine sediment (e.g., Li et al, 1999;Reed et al, 2002;Newberry et al, 2004;Inagaki et al, 2006;Takeuchi et al, 2009;Briggs et al, 2011;Durbin and Teske, 2011;Hoshino et al, 2011). Candidate bacterial phylum JS1 formed the most abundant group detected (3 of 17 clones) in the near-surface squeeze cake sample from Hole U1363G (Fig.…”
Section: Resultsmentioning
confidence: 86%
“…F4A). Candidate bacterial phylum JS1 formed the most abundant group detected in the surface raw sediment Sample 1363B1H1_RS (7 of 19 clones), where it was also most closely related to environmental gene clones recovered from other samples described here and in marine sediment worldwide (e.g., Li et al, 1999;Newberry et al, 2004;Briggs et al, 2011) (Fig. F4B).…”
Section: Resultsmentioning
confidence: 99%
“…2b; 11 from Riedel et al, 2006b; 1 from Briggs et al, 2011; and 7 from this study), only Core 5 from this study contained methane near the sediment-seawater interface. Thus, despite a large accumulation of gas and gas hydrate within meters of the seafloor (dashed grey line in Fig.…”
Section: Evidence For the Anaerobic Oxidation Of Methane (Aom) At Bulmentioning
confidence: 99%
“…(b) Coring locations from PGC01-03 ( ) and PGC02-08 ( ). Other piston cores taken in the area of Bullseye vent from previous studies are shown as black circles (Novosel et al, 2005;Riedel et al, 2006b) and black triangles (Briggs et al, 2011). The solid black line outlines the seafloor depression that defines the seep (Thomas et al, 2009).…”
mentioning
confidence: 99%
“…4b) decrease from interface to the anode surface. Moreover, as it has been proved by experiments [45,46] the major biofilm microorganisms are electrogens and for this simulation the mean value of electrogens to methanogens ratio is 5.94. The biofilm thickness varied dynamically from 11 micron to 14.6 micron over time (Fig.…”
Section: Evaluation Of the Model Mfc-related Partmentioning
confidence: 98%